1978
DOI: 10.1515/zna-1978-0320
|View full text |Cite
|
Sign up to set email alerts
|

Erzeugung und Untersuchung des Cyclopentadienons mit der Methode der temperaturabhängigen Photoelektronenspektroskopie / Preparation and Investigation of Cyclopentadienone by Variable Temperature Photoelectron Spectroscopy (VTPES)

Abstract: Using our VTPES technique cyclopentadienone is generated in the gas phase at 500-600 °C from the three different precursors cyclobutene-3,4-dicarboxylic acid anhydride, o-phenylene sulfite and o-benzoquinone and its PE spectrum is recorded. The PE spectrum and also the PE spectra of the various precursors as well as of the cyclopentadienone dimer are interpreted on the basis of our recently developed PERTCI method (i. e. performing large scale perturbation configuration interaction calculations in connection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Those observed in typical aldehydes and ketones [12] are nπ * , resulting from the excitation of a non-bonding electron to the anti-bonding π orbital in the carbonyl group, whereas in C 5 H 4 =O, the lowest lying electronic transition is a ππ * transition localised largely within the ring. The earlier, pioneering photoelectron studies [13,14] identified the ground state of the C 5 H 4 =O cation as X + 2 A 2 and the first excited states of the cation as A + 2 B 2 and B + 2 B 1 , as would be predicted from the molecular orbital diagram in Figure 1, thereby tending to corroborate the proposal that the highest occupied molecular orbital of the neutral is a π orbital in the ring of a 2 symmetry. Cyclopentadienone not only presents an interesting chemical problem with intriguing electronic structure questions, it is also a system with practical importance.…”
Section: Introductionmentioning
confidence: 59%
“…Those observed in typical aldehydes and ketones [12] are nπ * , resulting from the excitation of a non-bonding electron to the anti-bonding π orbital in the carbonyl group, whereas in C 5 H 4 =O, the lowest lying electronic transition is a ππ * transition localised largely within the ring. The earlier, pioneering photoelectron studies [13,14] identified the ground state of the C 5 H 4 =O cation as X + 2 A 2 and the first excited states of the cation as A + 2 B 2 and B + 2 B 1 , as would be predicted from the molecular orbital diagram in Figure 1, thereby tending to corroborate the proposal that the highest occupied molecular orbital of the neutral is a π orbital in the ring of a 2 symmetry. Cyclopentadienone not only presents an interesting chemical problem with intriguing electronic structure questions, it is also a system with practical importance.…”
Section: Introductionmentioning
confidence: 59%
“…At low pyrolysis temperatures (900–1100 K) the appearance of m / z 48 and m / z 80 indicate the conversion of o -phenylene sulfite to SO ( m / z 48) + CO ( m / z 28) + C 5 H 4 O ( m / z 80). The measured ionization energy (IE) of SO is 10.294 ± 0.004 eV, while that of C 5 H 4 O has been measured at 9.49 ± 0.02 eV and 9.40 eV . At higher pyrolysis temperatures (>1100 K), the C 5 H 4 O signal is attenuated and m / z 52, vinylacetylene (HCCCHCH 2 ), grows.…”
Section: Resultsmentioning
confidence: 99%
“…The Journal of Physical Chemistry A 52 (IE) of SO is 10.294 ± 0.004 eV, while that of C 5 H 4 O has been measured at 9.49 ± 0.02 eV 26 and 9.40 eV. 27 At higher pyrolysis temperatures (>1100 K), the C 5 H 4 O signal is attenuated and m/z 52, vinylacetylene 53 (HCCCHCH 2 ), grows.…”
Section: Calculationsmentioning
confidence: 97%
See 1 more Smart Citation